NIR-responsive mesoporous core-shell nanoplatform with oxygen self-supply and cascade targeting for reversing doxorubicin resistance via synergistic chemo-phototherapy - Yufeng Li; Yuping Jiang; Kexuan Wang; Xinyi Liu; Rui Yang; Lu Han; Tao He; Na Li; Da Huo (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Bioactive edestin peptides from hemp (Cannabis sativa L.) seeds improve exercise performance under hypobaric hypoxia - Rui Zhang; Jie Liu; Liang-Liang Chen; Jia-Qi Liu; Xiao-Qian Jin; Zi-Xian Fu; Jun-Bin Xiong; Bin Jia; Jun-Ling Shi; Da-Chuan Yin (Food Research International, 2026)

Incorporating Thermal Adaptation and Acclimation Improves Light‐Use Efficiency Modeling for Estimating Gross Primary Production in Tibetan Plateau Grasslands - Gaofei Yin; Jiangliu Xie; Yu Wang; Rui Chen; Yajie Yang; Dujuan Ma; Wenping Yuan; Qiaoyun Xie; Da Wei; Huai Chen; Xinwei Liu; Aleixandre Verger; et al. (Global Change Biology, 2026)
The optimal temperature for photosynthesis (Topt), the temperature at which photosynthesis peaks, is crucial for estimating gross primary production (GPP). Most models, however, apply biome‐specific Topt, overlooking the spatial and temporal variability driven by the genetic adaptation and interannual thermal acclimation of plants, thus introducing systematic error in GPP estimation. We mapped Topt of Tibetan Plateau (TP) grassland averaged over 1982–2018, using satellite‐derived near‐infrared reflectance of vegetation as a proxy of photosynthesis, and projected future Topt under different scenarios of shared socioeconomic pathways (SSPs) using space‐for‐time substitution. We assessed the effects of Topt adaptation on current GPP estimation and acclimation on projected GPP using a light‐use efficiency model (i.e., EC‐LUE model). The spatial heterogeneity of Topt was pronounced across the TP grassland, with higher values in the northeast and lower values in the southwest, averaging 9.32°C ± 3.15°C. Topt tended to increase from 2040 to 2080 across all SSPs, with the slowest increase under SSP1‐2.6 (0.015°C y −1 ) and the fastest increase under SSP5‐8.5 (0.061°C y −1 ). Incorporating Topt adaptation into the EC‐LUE model improved the accuracy of GPP estimation, with R 2 increasing by 7.19% and RMSE decreasing by 11.40%, compared to the model with a fixed Topt. In contrast, ignoring the adaptation of Topt led to systematically lower GPP values across 77.9% of the TP grassland, resulting in an overall reduction of estimated GPP by 7.07% (0.07 g C m −2 d −1 ). Ignoring the acclimation of Topt led to systematically higher projected GPP on the TP, ranging from 2.87% ± 8.96% (SSP1‐2.6) to 3.83% ± 5.97% (SSP3‐7.0) across different scenarios, covering more than 70% of TP regions. These findings highlight the necessity of incorporating both the adaptation and acclimation of Topt into GPP models to enhance the monitoring of the carbon cycle.

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Hydration-driven structural engineering via enzymatic glycation: Sustained quercetin release in pullulan-zein coatings for extended walnut preservation - Zi-han Wang; Xue-li Liu; Rui-qi Sun; Bin Qi; Jun-xia Xia; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2026)